Penerapan Model Pembelajaran Reciprocal Teaching untuk Meningkatkan Motivasi dan Hasil Belajar Keterampilan Komputer dan Pengolahan Informasi (KKPI) Siswa Kelas X.AP di SMK Nusa Dua Sawan Tahun Ajaran 2012/2013 - Ni Made Budi Ratiningsih SW; I Gede Sudirta; I Gede Mahendra Darmawiguna (Universitas Pendidikan Ganesha, 2013)
This study was aimed to (1) know the students’ learning motivation result of X.AP class at SMK Nusa Dua Sawan in 2012/2013 of Computer skill and information processing (CSIP), (2) know the students’ learning result of X.AP class at SMK Nusa Dua Sawan in 2012/2013 of computer skill and information processing (CSIP) lesson using reciprocal teaching learning model; (3) know the students’ response of X.AP class to apply the reciprocal teaching model of computer skill and information processing (CSIP). This study is a classroom action research design that used in 2 cycles by involving a total Number of 35 students of X.AP class at SMK Nusa Dua Sawan first semester in 2012/2013. The object of this research emphasized on the students motivation, result and students response in basic competency to operated text principle sistem of computer skill and information processing (CSIP). The learning students result data was collected based on cognitive test and affective observation. Meanwhile,the students’ response and motivation data was collected by using questionnaire. The obtained data were analyzed descriptively. The result of the study showed that (1) there was improvement of learning students’ result of X.AP class at II cycle to apply the reciprocal teaching model of computer skill and information processing (CSIP). the results indicated that the learning students result score include: averaging class, and classical completeness learning students was improvement (2) there is improvement of learning motivation students’ by apply the reciprocal teaching learning (3) the students’ responses towards reciprocal teaching model of computer skill and information processing (CSIP) is really positive.